Rola osób z najwyższego kierownictwa w kształtowaniu aktywności innowacyjnej regionalnych browarów w Polsce - Jasińska, Alicja (Top Management's Role in Running Innovation Activity in Regional Breweries in Poland, 2008)
This study tries to point at the role of top management in running innovation activity in regional breweries in Poland. It is based on the author's own research results concerning the period between 2005 and 2006. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 57-66